Effects of bacterial endophytes from potato roots and tubers on potato cyst nematode (Globodera rostochiensis) - NOOR ISTIFADAH; NURHAYATI PRATAMA; SYAHRIZAL TAQWIM; TOTO SUNARTO (Society for Indonesian Biodiversity, 2018)
Istifadah N, Pratama N, Taqwim S, Sunarto T. 2018. Effects of bacterial endophytes from potato roots and tubers on potato cyst nematode (Globodera rostochiensis). Biodiversitas 19: 47-51. Bacterial endophytes are bacteria that inhabit plant tissues without causing any diseases. The endophytes existence may have negative, neutral, or positive effects on the host plants. This paper discusses the effects of bacterial endophytes isolated from potato roots and tubers on potato growth and their abilities to suppress potato cyst nematode, Globodera rostochiensis. The bacterial endophytes were isolated from roots and tubers of potatoes obtained from six plantation areas in West Java. The endophyte isolates were examined for their effects on potato growth. The non-pathogenic isolates were tested for their abilities to suppress G. rostochiensis in vitro and in potato plants. The results showed that from 88 bacterial endophyte isolates obtained, 13 isolates caused rot in potato seed pieces, 22 isolates inhibited the potato growth, while, 2 isolates increased the growth, and as many as 51 isolates did not influence the growth. The in vitro test using the isolate culture filtrate revealed that there were seven isolates that caused mortality of G. rostochiensis juvenile-2 by 67.5-97.7%. These isolates, however, were not effective in damaging the nematode eggs. In the greenhouse experiment, the bacterial endophyte isolates suppressed the number of cysts by 51.7-65.4% and that of the juvenile-2 of G. rostochiensis by 48.6-76.4%.